Device-Guided Slow-Paced Respiration for Menopausal Hot Flushes: A Randomized Controlled Trial. Issue 5 (May 2015) - Huang, Alison J.; Phillips, Sara; Schembri, Michael; Vittinghoff, Eric; Grady, Deborah
Abstract : OBJECTIVE: To evaluate the efficacy of device-guided slow-paced respiration for reducing the frequency and severity of menopausal hot flushes. METHODS: Perimenopausal or postmenopausal women reporting four or more hot flushes per day were recruited into a parallel-group, randomized trial of slow-paced respiration using a portable guided-breathing device. Women were randomly assigned to use a standard device to practice slowing their resting breathing rate to less than 10 breaths per minute for at least 15 minutes everyday or use an identical-appearing control device programmed to play relaxing nonrhythmic music while monitoring spontaneous breathing. The primary outcome, change in hot flush frequency over 12 weeks, was assessed using data from validated 7-day diaries abstracted by blinded analysts. RESULTS: Among the 123 participants, mean age was 53.4 (±3.4) years. Women reported an average of 8.5 (±3.5) hot flushes per day at baseline. After 12 weeks, women randomized to paced respiration (n=61) reported an average reduction of 1.8 (95% confidence interval [CI] 0.9–2.6) hot flushes per day (−21%) compared with 3.0 (95% CI 2.1–3.8) hot flushes per day (−35%) in the music-listening group (n=62) ( P =.048). Paced respiration was associated with a 19% decrease in frequency of moderate-to-severe hot flushes compared with a 44% decrease with music listening ( P =.02). CONCLUSION: In this randomized trial, women assigned to device-guided slow-paced respiration reported modest improvements in the frequency and severity of their hot flushes, but the paced respiration intervention was significantly less effective than a music-listening intervention in decreasing the frequency and severity of these symptoms. CLINICAL TRIAL REGISTRATION: Clinicaltrials.gov, www.clinicaltrials.gov, NCT01466998. LEVEL OF EVIDENCE: I Abstract : As a behavioral treatment strategy, slow-paced respiration is less effective in reducing the frequency and severity of menopausal hot flushes than listening to relaxing music.